Advances in industrial and labor relations - Kaufman, Bruce E.; Lewin, David 1943- (Emerald, 2005)
Volume 14 of Advances in Industrial and Labor Relations (AILR) contains 10 papers dealing, respectively, with HR versus finance in the control of corporate health care decisions; a theory of workplace conflict grounded in U.S. municipal collective bargaining; creative compliance in, or union defiance of, labor regulation in Australia; the extent to which union organizing means determine bargaining ends; the failure of labor-manangement cooperation at two Maine (U.S.) paper mills; the interplay between union and nonunion representation arrangements at Eurotunnel; challenges to and prospects for the industrial relations field in France; an empirical and comparative analysis of the industrial relations field in Germany; the development of the industrial relations field in Canada; and the implications of a decentralized labor market for industrial relations as a field in Australia. Taken together, these papers feature a rich mix of theory and empiricism, quantitative and qualitative analyses, and international perspectives on both industrial relations and human resources. Four of the papers were winners of the 2004 and 2005 AILR/Labor and Employment Relations Association Competitive Papers Competitions, and all papers were subject to double blind anonymous refereeing. The papers in Volume 14 of AILR will be of interest to industrial relations and human resource scholars and practitioners worldwide.
Contains 10 papers dealing with HR versus finance in the control of corporate health care decisions; a theory of workplace conflict grounded in US municipal bargaining; creative compliance in, or union defiance of, labor regulation in Australia; and more. This title is for industrial relations and human resource scholars and practitioners.